Development of a Post-Processing Procedure to Characterize Damage in Hybrid Natural Woven Composites Subjected to Low-Velocity Impact by Means of Thermography Techniques - Tiziana Matarrese; Claudia Sergi; Davide Palumbo; Fabrizio Sarasini; Umberto Galietti (Engineering Proceedings, 2025)
The active thermographic techniques are well-established for controlling composite components subjected to low-velocity impact damage. However, in recent years, the main works on thermographic techniques have focused on processing the raw data with the aim of increasing the signal-to-noise ratio and the probability of damage detection. It is well-known that assessing the residual strength of the material is crucial for quantifying the damage extension. In this regard, the aim of this work is to quantify the damage produced by impacted tests on hybrid woven composites by means of thermographic techniques. In particular, a novel procedure based on applying two filters frame by frame on the thermographic data obtained after applying the pulse thermographic technique was proposed, and information about the damage extension was provided. The results showed the possibility of quantitively estimating the damage and the effect of momentum in hybrid natural fiber composites.